The Khoisan Revivalist Movement and the Decolonial Turn: Authenticity, naming and cultural identities in Khoisan historiography for epistemic justice - Rakei, Simon (WritingThreeSixty: Journal or Research and Creative Text, 2021)
The Khoisan revivalist movement has its roots in rejecting the term Coloured as an oppressive colonialist and apartheid imposition. As illustrated by Verbuyst and Bam, it is a movement of claiming identity and belonging. In this respect, the essay establishes the operative discursive framework of Khoisan historiography. Part 1 illustrates how the history which the Khoisan revival movement seeks to connect to – to affirm and demarginalize its cultural identity in contemporary South Africa – has been severely sullied by racism and its antecedent in the form of the temporal discourse of anthropology. The essay thus hopes to unpack the trappings for Khoisan historiography ordered by the temporal discourse of anthropology: this might mean not only an erasure of history, but a broader estrangement from the history the Khoisan revival movement seeks out in Southern Africa and Africa more broadly. The second part of the essay borrows from William Elis’s tracing of genealogies and narratives of San authenticities, to attempt to envision what an epistemically just Khoisan historiography in relation to Southern Africa might look like. The essay concludes by drawing on what these connections might mean not only for Khoisan historiography and the archives it could draw from, but for the Khoisan revival movement itself.